Workshop Praktek Pemberian Makanan Pendamping ASI (MP-ASI) bagi Baduta pada Kader Posyandu - Dwi Erma Kusumawati; Ansar, Ansar; Bahja, Bahja; Fahmi Hafid (Poltekita: Jurnal Pengabdian Masyarakat, 2020)
Stunting is a nutritional problem which its overcoming effort should be started from thousand days of early life. Age of 6 to 24 months is a golden life phase that when its nutritional fulfillment are insufficient, it will give a big impact for the future life. On this phase, the childs are started for recognition of breastmilk complementary food which its texture and amount are different based on the age. There are still many problems in Indonesia regarding the golden standard implementation of infant and child feeding such as Early Breastfeeding Initiation, Exclusive Breastfeeding, and Breastfeeding till 24 months or more. Workshop using andragogy training technique in rilex but serious situation is expected to increase knowledge of training material. Workshop is conducted by utilizing the available space with group dynamics and games. The results of public service activity with 24 cadres as participant showed that there are 20 cadres that increase their knowledge after attending workshop and there are 4 cadres that there is no change in knowledge. Wilcoxon test showed p value as 0.001. This is indicate that statistically there is a significant different of knowledge after attending workshop. The common child and infant feeding practice in our community is early complementary feeding with excuses that breastmilk is not enough to increase baby weight and food taboo such as forbidden for consumption of milk banana.